"Owning" the personal past: Adolescents' and adults' autobiographical narratives and ratings of memories of recent and distant events. Issue 2 (7th February 2016) - Bauer, Patricia J.; Hättenschwiler, Nicole; Larkina, Marina
Abstract : Adults and adolescents are characterised as having different perspectives on their personal or autobiographical memories. Adults are recognised as having vivid recollections of past events and as appreciating the meaning and significance of their autobiographical memories. In development, these qualities are noted as absent as late as adolescence. To evaluate the assumption of developmental differences, we directly compared autobiographical memories of adults and adolescents drawn from each of several periods in the past, using measures of narrative quality (coded independently) and participants' own subjective ratings of their memories. Adults' narratives of events from the previous year and for the "most significant" event of their lives were coded as more thematically coherent relative to those of adolescents'; the groups did not differ on thematic coherence of narratives of early-life events (ages 1–5 and 6–10 years). The ratings that adults and adolescents provided of their autobiographical memories were similar overall; differences were more apparent for early-life events than for more recent events and indicated stronger mnemonic experiences among adolescents than adults. The pattern of findings suggests that whereas adults have more sophisticated narrative tools for describing the significance of events and their relation to the corpus of autobiographical memories, adolescents as well as adults have vivid recollective experiences as well as personal and subjective perspective on the events of their lives and their memories thereof.